Headache Phenotype and the Psychosocial Burden of Cluster Headaches: An Analysis of Patients Prior to Hospitalization - Carl Hartmut Göbel; Britta Koch; Katja Heinze-Kuhn; Axel Heinze; Anna Cirkel; Hartmut Göbel (Pain and Therapy)
Abstract Introduction The specific headache phenotype, accompanying symptoms and psychological impact that lead to admission of patients with cluster headache are not yet known. The aim of this study was therefore to analyze the characteristics of patients who were admitted to a tertiary headache center in 2018, 2019 and 2020 due to cluster headache. Methods A total of 207 patients with cluster headache were examined, who were admitted to the Kiel Headache Center, a tertiary headache center in Germany, in the years 2018, 2019, and 2020. A retrospective cohort study was conducted to analyze the phenotype and psychosocial impact of cluster headaches in a standardized manner. The data were collected based on information from the standardized Kiel Headache Questionnaire, the Migraine Disability Assessment (MIDAS) questionnaire, and the World Health Organization (WHO) Disability Assessment Schedule (WHODAS 2.0). Results Most of the patients had a chronic course of disease over many years, and 71.5% had had the disease for more than 5 years. Cluster headache attacks occurred in 98.6% of the patients, with strong to very strong pain intensity, and more than 78% of the patients experienced three or more attacks per day. Nighttime occurrence led to severe sleep disturbances with exhaustion, a lack of energy, and an inability to work. In 31.4% of the patients, persistent pain in the area also contributed to the inability to work. A total of 94.7% of the patients had a MIDAS score of grade 4. The analysis of the WHODAS 2.0 score revealed that 92.7% of the patients with cluster headaches experienced severe limitations in their health and functionality. These individuals were particularly severely affected by the accompanying psychological symptoms and the psychosocial impact of cluster headaches. The highly stressful complications of cluster headaches were particularly evident in the high frequency of suicidal ideation in more than 40% of the patients examined. Severe illness affected almost all areas of professional, social, and family life and caused a very high level of suffering. Conclusions The results revealed a pronounced, severe symptom complex in patients with cluster headaches that went far beyond the purely diagnostic criteria. The psychosocial impact of cluster headaches should be given close attention in the care of these patients.